Taylor Swift versus Mozart: music preferences of C57BL/6J mice - Kamionek, Dominik; Maaß, Johann; Pitzer, Claudia; Schaaf, Christian P. (Frontiers in behavioral neuroscience, 2025)
IntroductionMusic has become an established complementary element of modern medicine, demonstrating beneficial effects towards various diseases such as dementia, hypertension, or chronic pain. Given its low cost and non-invasive nature, music-based interventions have been studied in both healthy mice and disease models over recent decades to examine potential effects in rodents. However, the selection of music in these interventions is based on prior reports and human preferences, without critically evaluating its relevance or perception in mice. Novel experimental approaches are needed to evaluate which type of music is preferred by mice.MethodsIn this pilot study, we introduce a new experimental setup that can be used to analyze the music preferences regarding different genres and frequencies. Here, we present the first-ever evaluation of mouse music preferences by examining the behavioral responses of healthy C57BL/6J.ResultsWhen given a choice between different musical conditions, mice spent comparatively less time in a chamber playing Sonata for Two Pianos in D major, K.448 by Mozart, a piece regularly used in music-intervention studies of rodents. Further testing revealed that this behavioral response is independent of tone pitch.DiscussionThese findings underscore the importance of species-specific tailoring of music selection towards therapeutic approaches. Our assay can be used to further broaden our understanding of murine music preferences and to analyze how mice respond to and perceive different auditory stimuli. Further studies are needed to systematically investigate murine music perception and preference across genres and exposure durations.
Veröffentlicht: 15. Oktober 2025
Gesehen am 03.12.2025